Realization of Positive and Negative Politeness as maneuvering strategies in Austen’s Pride and Prejudice - Salman, Hawraa T.; Yusoff, Zailin Shah Binti (Technium Social Sciences Journal, 2021)
Literature is that vast field of knowledge, accents and entertainment. Therefore, it is considered one of the most significant ways of expressing social relations and cultures. Nevertheless, readers of literary works could be deceived by delusional ways some writers adopt in portraying the characters of their literary works. Austen employs strategic maneuvering to persuade her readers towards her perspectives. The researcher chooses Jane Austen’s Pride and Prejudice to be analyzed pragmatically to clear up the underlying intentions and maneuvering tactic of some of the prominent characters of the novel. Accordingly, in Pride and Prejudice, Austen uses positive and negative politeness strategies as maneuvering strategies to show gender difference. Descriptive qualitative is used in this research. Politeness strategies is used widely by all the characters for different purposes, however, some of them mange to get the wanted goals. The researcher only focuses on main characters. Analyses reveal that male tend to use positive politeness, whereas female tend to use negative politeness. Both of them use on record and off record politeness strategies.